Desmoid tumour, a rare tumour in oncology practice: A case series and literature review (Annals of Medical Research, 2021)
Aim: Desmoid tumors (DTs) are very rare tumors that grow gradually anywhere in the body they are locally aggressive, but with a low potential for metastasis. Very good results can be obtained with different combinations of treatments, such as surgery, chemotherapy, hormonal therapy, tyrosine kinase inhibitor therapy and radiotherapy. Case series even with a small number of patients are of considerable importance as experience with DTs limited. Therefore, in this study, we aimed to discuss the management of DTs with our case series.Materials and Methods: In our study, 15 patients with DT, who were treated and followed up between January 2005 and January 2020 in two hospital medical oncology departments in Turkey, were evaluated.Results: The median age of diagnosis of the patients was 34 (range 18-48) years. Seven (46.6%) of the patients were female and eight (53.4%) were male. Seven (46.6%) of the tumors were located in the abdominal wall, four (26.7%) were in the limbs three (20%) were in the intra-abdominal area, and one (6.7%) was in the chest wall. In terms of resectability, 14 (93.3%) were resectable, and one (6.7%) was unresectable. The five-year overall survival rate was 73.85%, and the average disease-free survival time until relapse was 35 (range 15-83) months in patients who relapsed. The two- and five-year relapse-free survival rates were 90.9% and 66.5%, respectively. The  edian progression-free survival (PFS) for first-line treatment was 25 (range 8.6-89.8) months. The median PFS for second-line treatment was seven (range 4.3-38.0) months. In the one patient who received third-line treatment, PFS was 8.3 months.Conclusion: Frequent relapses in DTs are still the biggest problem in treating this disease. Although surgery treatment is the main  treatment method used in desmoid tumors, controversy about adjuvant therapy after surgery continues, and new treatment modalities are required.
Keywords: Desmoid tumors; recurrence; sulindac; survival; tamoxifen